The Slither sisters - Gilman, Charles (Gilman, Charles. Tales from Lovecraft Middle School, 2013)
Twins Sarah and Sylvia Price, two monsters in disguise at Lovecraft Middle School, are campaigning for student council with a secret plan to abduct the entire seventh grade, and Robert Arthur and his strange friends must stop their evil plot.